2017
DOI: 10.1523/jneurosci.2006-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Circadian Rhythms and Synchrony in the Suprachiasmatic Nucleus

Abstract: In mammals, the suprachiasmatic nucleus (SCN) of the hypothalamus coordinates daily rhythms including sleep-wake, hormone release and gene expression. The cells of the SCN must synchronize to each other to drive these circadian rhythms in the rest of the body. The ontogeny of circadian cycling and intercellular coupling in the SCN remains poorly understood. Recent in vitro studies have recorded circadian rhythms from the whole embryonic SCN. Here, we tracked the onset and precision of rhythms in PERIOD2 (PER2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 66 publications
3
88
1
Order By: Relevance
“…Accordingly, the VIP‐like immunoreactivity has also been detected in cells and fibers of the rat SCN prior to birth, although the neurons appear to be morphologically immature, and their distribution differs from that seen in the adult SCN (Laemle, ). Surprisingly, in a recent study, an absence of the VIP and its receptors (VIPAC2R) in the fetal mouse SCN was reported (Carmona‐Alcocer et al., ).…”
Section: Morphological Development Of the Scnmentioning
confidence: 98%
“…Accordingly, the VIP‐like immunoreactivity has also been detected in cells and fibers of the rat SCN prior to birth, although the neurons appear to be morphologically immature, and their distribution differs from that seen in the adult SCN (Laemle, ). Surprisingly, in a recent study, an absence of the VIP and its receptors (VIPAC2R) in the fetal mouse SCN was reported (Carmona‐Alcocer et al., ).…”
Section: Morphological Development Of the Scnmentioning
confidence: 98%
“…Circadian oscillations of the core clock genes are also evident in the late stage of gestation. Recent studies have shown circadian oscillations of Per2 Luc reporter expression in ex vivo cultures of fetal mouse SCN slices isolated at E14.5 or later, corresponding to the crucial period for SCN development and neurogenesis 29–31 . Peripheral circadian oscillators also develop during ontogeny 32 .…”
Section: Emergence Of the Circadian Clock During Ontogenesismentioning
confidence: 99%
“…These reports strongly suggest that fetal peripheral tissues and cells spontaneously develop self‐sustaining circadian gene expression rhythms without maternal signals. In contrast to peripheral tissues, the SCN explanted at E13.5 is reported to be arrhythmic and to remain arrhythmic during the course of ex vivo culture, suggesting that signals from the environment might be required for the development of the master circadian regulator in the SCN 31 …”
Section: Emergence Of the Circadian Clock During Ontogenesismentioning
confidence: 99%
“…However, mutant mice that lack connexins, or those lacking VIP or the VIP receptor, do not show complete abolishment of coupling (Herzog et al, 2017). Similarly, a recent study of the ontogeny of SCN synchrony indicated that such synchrony appears prior to the expression of VIP (Carmona-Alcocer et al, 2018). Therefore, it is parsimonious to conclude that the DDCS network, with its high preference for ipRGC input, offers a plausible network motif within the SCN to enhance the effect of ipRGC signals, thus achieving a strong response within this nucleus to light input.…”
Section: Iprgc Axons Within Different Brain Regions Have Structurallymentioning
confidence: 99%